Struktur Komunitas Plankton di Beberapa Jenis Kolam Ikan Lele (Clarias batrachus) - Ramadansur, Rahmat; Laurenza, Laura; Dinata, Marta; Sembiring, Al Khudri; Akbar, Muhammad Azhari (Jurnal Biologi Universitas Andalas, 2024)
The plankton community structure is a collection of zooplankton and phytoplankton populations that interact with each other in a waters. This study aims to analyze the structure of the plankton community and the influence of environmental conditions (physico-chemical) on the structure of the plankton community in the ponds. The research sample was taken using a purposive sampling method, which represents three types of catfish ponds, namely, earthen ponds, tarpaulins, and biofloc. The results showed that in the three types of ponds studied, there were two species of zooplankton and 45 species of phytoplankton. Phytoplankton in soil ponds was dominated by Stigeoclonium subsecundum. Meanwhile, the zooplankton was dominated by Nebela collaris. Diversity (H') of zooplankton is in the low category with polluted water quality in the three ponds, while phytoplankton is in the high-low category. The equitability index (E) of zooplankton is in the stable category, while phytoplankton is in the depressed-stable category. The dominance index (D) of zooplankton belongs to the medium-low category, while phytoplankton belongs to the low category. As for the physico-chemical parameters of the waters, the three types of ponds have different effects from each parameter tested on the structure of the plankton community.